Line‐assisted complete closure for a large mucosal defect after colorectal endoscopic submucosal dissection decreased post‐electrocoagulation syndrome. Issue 5 (29th April 2018) - Yamasaki, Yasushi; Takeuchi, Yoji; Iwatsubo, Taro; Kato, Minoru; Hamada, Kenta; Tonai, Yusuke; Matsuura, Noriko; Kanesaka, Takashi; Yamashina, Takeshi; Arao, Masamichi; Suzuki, Sho; Shichijo, Satoki; et al.
Abstract : Background and Aim: The incidence of post‐endoscopic submucosal dissection (ESD) coagulation syndrome (PECS) can be decreased by closing mucosal defects. However, large mucosal defects after colorectal ESD cannot be closed endoscopically. We established line‐assisted complete clip closure (LACC), a novel technique for large mucosal defects after colorectal ESD. We evaluated the prophylactic efficacy of LACC for preventing PECS. Methods: Sixty‐one consecutive patients on whom LACC after colorectal ESD was attempted from January 2016 to August 2016 were analyzed. After exclusion of patients with incomplete LACC and adverse events during ESD, 57 patients comprised the LACC group. In contrast, 495 patients who did not undergo closure of a mucosal defect comprised the control group. Propensity score matching was used to adjust for patients' backgrounds. Treatment outcomes were evaluated between the groups. Results: Median resected specimen size in the LACC‐attempted group was 35 mm (range, 20–72 mm), and LACC success rate was 95% (58/61). Median procedure time of LACC was 14 min. In the LACC group, incidence of PECS was only 2%, and no delayed bleeding or perforation occurred. Propensity score matching created 51 matched pairs. Adjusted comparisons between the LACC and control groups showed a lower incidence of PECS (0% vs 12%, respectively; P = 0.03) and shorter hospitalization (5 vs 6 days, respectively; P < 0.001) in the LACC group. Conclusion: This study suggests that LACC can effectively reduce the incidence of PECS, although further large‐scale studies are warranted.